A Colheita do Senhor Absoluto: o problema da morte na filosofia de Hegel - Piasecki, Dennis Donato (2014)
The present dissertation aims to investigate the concept of death in the philosophy of Hegel. More precisely, it seeks to understand how the issue unfolds the problematic of death within the Hegelian system. Reading has undertaken here as a propositional guiding the determination that death, i.e., the absolute manifestation of contingency of finite beings, is a phenomenon necessary for the formation of the system itself. Thus it is intended to demonstrate the impossibility of considering the meaning of death, as found in the Hegelian text, only in the one-sidedness of his contingency sense, but that one must also understand the necessity of death as the supersession of contingency for speculative development of the spirit. To demonstrate such a reading, I will explore in the first chapter of this work on the role that contingency occupies in Hegel's philosophy; in the second chapter I will determine the meaning of ontological death and ontic death and the bond with the latter with the figure of aufheben as a supression and the sublation of contingency, and; finally, in the third chapter I will analyze the extent to which the theme of the death of God, as developed by Hegel, reconciles the ontological sense (systematic) and ontic (empirical) of death from the representation of the absolute death.